INTERPRETATION OF THE THEME OF HOMELAND IN POETRY AND ITS PURPOSE (Conferencea, 2023)
In this article, the interpretation of the motherland theme in iqbol mirzo's poetry, Mirzo's poetry is about independence and patriotism, and the idea that the Motherland is a person's loyalty to the land where he was born and raised.